SAT0060 Best Chance of Achieving Remission in RA Patients with Very Short Disease Duration. (10th June 2014) - Uhlig, T.; Norvang, V.; Lie, E.; Rødevand, E.; Mikkelsen, K.; Lexberg, Å. S.; Kalstad, S.; Kvien, T.K.
Abstract : Background: Clinical remission (REM) is the treatment target in rheumatoid arthritis (RA), and there are several composite REM criteria available. Knowledge is limited on how disease duration affects REM in daily clinical practice, and whether predictors of REM depend on the method for assessment of REM. Objectives: To study the rates of REM after 3 and 6 months with DMARD treatment applying different criteria, and to study predictors of REM after 6 months. Methods: Data from 4992 patients in the NOR-DMARD study, representing real life rheumatology practice, were analysed. All patients started with a synthetic or biological DMARD and had 6-month follow-up data available, . Mean (SD) age was 54.6 (14.9) yrs, disease duration was 8.5 (7.9) yrs, 73.2% females. Disease duration (mean 7.9 [9.6] yrs) was grouped into: <0.5 yrs (n=1329), >0.5-1 yr (n=321), >1-5 yrs (n=992), >5-10 yrs (n=750), and >10 yrs (n=1532). The applied definitions for clinical REM were Disease Activity Score28 (DAS28) <2.6, Simplified Disease Activity Index (SDAI) ≤3.3, Clinical Disease Activity Index (CDAI) ≤2.8, Routine Assessment of Patient Index Data (RAPID3, range 0-10) ≤1, and the Boolean ACR/EULAR REM definition (BOOL) ≤1, with additional BOOL for practical use (BOOLP) ≤1. Results: Overall REM rates after 3 (6) months were for DAS28 22.5 (26.0)%, CDAI 10.3 (12.6)%, SDAI 9.8 (11.8)%, RAPID3 20.3 (21.3)%, BOOL 8.7 (10.1)%, and BOOLP 10.3 (12.2)%. Both at 3 and 6 months REM rates were highest for disease duration <0.5 yr for all six composite definitions (ANOVA all <0.001), varying from BOOL 12.5% (3 mths) to DAS28 34.3% (6 mths), with lower rates and minor changes across higher disease duration groups. The table shows odds ratios (*p<0.05 **p<0.01 ***p<0.001) for achieving 6-month REM in separate logistic regression models for each remission definition, adjusting always for age, respective baseline disease activity as well as other covariates (the latter were included in the multivariable model if p<0.10). Conclusions: In clinical practice REM within 6 months of start/change of therapy was most frequently achieved if baseline disease duration was ≤0.5 year. REM at 6 months is further independently predicted by use of biologic DMARDs, lower age, higher education, non-smoking, absence of erosions, lower baseline disease activity, lower fatigue score, and better physical function. These real life findings inform clinicians on optimal patient treatment, including the need for very early use of DMARDs. Disclosure of Interest: T. Uhlig Consultant for: AbbVie, BMS, MSD, Pfizer, Roche, UCB, V. Norvang: None declared, E. Lie Consultant for: AbbVie, BMS, Hospira, Pfizer, UCB, Speakers bureau: AbbVie, BMS, Pfizer, Roche UCB, E. Rødevand: None declared, K. Mikkelsen: None declared, Å. Lexberg: None declared, S. Kalstad: None declared, T. Kvien Consultant for: AbbVie, BMS, Celltrion, Eli Lilly, Hospira, MSD/Schering-Plough, Orion Pharma, Pfizer/Wyeth, Roche, UCBAbbVie, BMS, Hospira, Pfizer, UCB, Speakers bureau: AbbVie, BMS, Celltrion, Eli Lilly, Hospira, MSD/Schering-Plough, Orion Pharma, Pfizer/Wyeth, Roche, UCB DOI: 10.1136/annrheumdis-2014-eular.2411